The effectiveness of singing in improving primary students' memorizing in the subject of science at SK. Bukit Lanjan (Asli) Selangor / Suzianah Abdul Talib - Abdul Talib, Suzianah (2015)
Science is a subject that involves students to memorize and remember numerous facts, scientific names, labeling and so on. A suitable approach in teaching Science which should counter the needs of modern students should be implemented so that the activities during the teaching and learning process would satisfy the students' needs and thus giving the maximum impact. Realizing the fact that students love music and singing, I have implemented this method in carrying out activities in the teaching and learning of Science. My chosen research respondents are 20 students from Year 4 class of Sekolah Kebangsaan Bukit Lanjan (Asli). This research is done to ensure the effectiveness of music and songs to improve the students' memorizing skills and the topic while doing the research is "Animals Life Process" - The Life Cycle of a Frog. The instruments that I have used were Pre Test, as well as questionnaires. Based on the analysis done after the Pre Test, observation and questionnaires , teaching through songs in the teaching and learning process in Science was able to attract students' interest to study as well as creating condusive learning atmosphere in the classroom. Result of this research indicated that teaching Science through songs has succeeded in helping the students to recall the topic that they had learnt, that is, "Life Cycle of a Frog", better.